Bacteria-based repair and self-healing of concrete. Issue 1 (8th March 2016) - De Belie, N.; Wang, J.
Abstract : Durability problems in concrete can often be linked to a high permeability, which is either caused by a high matrix permeability or the presence of cracks. Therefore, treatments that reduce the permeability of the matrix, or that close the crack from ingress of aggressive agents carried by water or air, would substantially enhance the service life of a concrete structure. Several chemical products are currently in use for consolidation and crack repair, but a new technique that has been the focus of much research efforts over the last decade is the bacteria-based calcium carbonate precipitation. This technique is now slowly making its way towards practical applications. The principles of the technique, the important influential parameters and the recent advances related to its use for consolidation, surface protection, external crack repair, and self-healing of cracks in concrete are discussed in this article. Also the wider applicability for mechanical strengthening and consolidation of natural stone and soils is shortly treated.